Changes in motor function and quality of life after surgery in patients with pancreatic cancer. (26th November 2020) - Nakashima, Yuki; Kawae, Toshihiro; Iwaki, Daisuke; Fudeyasu, Kenichi; Kimura, Hiroaki; Uemura, Kenichiro; Okamura, Hitoshi
Abstract: Objective: To determine the changes in motor function and health‐related quality of life after pancreatectomy and identify factors influencing postoperative physical functioning in health‐related quality of life. Methods: This single‐centre, prospective, observational study measured 6‐min walking distance, grip strength, knee extension strength and health‐related quality of life variables in patients with pancreatic cancer, before and after surgery. Paired t‐ and Wilcoxon signed‐rank tests were used to compare pre‐ and postoperative motor function and health‐related quality‐of‐life variables. Factors associated with postoperative physical functioning scores of health‐related quality of life were assessed using multiple regression analysis. Results: Fifty‐nine individuals were enrolled. Motor function values decreased significantly postoperatively, including 6‐min walking distance (mean ± standard deviation: 402.5 ± 95.4 vs. 497.7 ± 80.4 m, p < 0.001), knee extensor strength (0.42 ± 0.10 vs. 0.47 ± 0.10 kgf/kg, p < 0.001) and grip strength (22.0 ± 8.9 vs. 24.5 ± 9.2 kg, p = 0.001). Multiple regression analysis showed significant association between 6‐min walking distance change and postoperative physical functioning scores of health‐related quality of life ( p = 0.036). Conclusion: The results suggest that motor function decreases postoperatively, and a decrease in 6‐min walking distance after surgery is associated with postoperative physical functioning in patients with pancreatic cancer.